Divergence-Based Introgression Polarization. (27th March 2020) - Forsythe, Evan S; Sloan, Daniel B; Beilstein, Mark A
Abstract: Introgressive hybridization results in the transfer of genetic material between species, often with fitness implications for the recipient species. The development of statistical methods for detecting the signatures of historical introgression in whole-genome data has been a major area of focus. Although existing techniques are able to identify the taxa that exchanged genes during introgression using a four-taxon system, most methods do not explicitly distinguish which taxon served as donor and which as recipient during introgression (i.e., polarization of introgression directionality). Existing methods that do polarize introgression are often only able to do so when there is a fifth taxon available and that taxon is sister to one of the taxa involved in introgression. Here, we present divergence-based introgression polarization (DIP), a method for polarizing introgression using patterns of sequence divergence across whole genomes, which operates in a four-taxon context. Thus, DIP can be applied to infer the directionality of introgression when additional taxa are not available. We use simulations to show that DIP can polarize introgression and identify potential sources of bias in the assignment of directionality, and we apply DIP to a well-described hominin introgression event.